An assessment of wide-lane ambiguity resolution methods for multi-frequency multi-GNSS precise point positioning. Issue 374 (2nd September 2020) - Duong, V.; Harima, K.; Choy, S.; Laurichesse, D.; Rizos, C.
Abstract : We assess the time-to-first-fix (TTFF) and the ambiguity fixing rate of two PPP wide-lane ambiguity resolution (WL-AR) methods, namely the geometry-based and ionospheric-free (GB-IF) method, and the geometry-free and ionospheric-free (GF-IF) method. First, an optimal GF-IF WL linear combination is selected based on the ratio between the code and carrier phase measurement noise ( R T ). Then, the relation between ambiguity variance and satellite geometry in the GB-IF WL-AR is investigated. Both simulated and real data from 31 GNSS stations over 37 consecutive days in 2017 were used. Numerical results show that the GF-IF WL-AR method has shorter TTFF and higher ambiguity fixing rate compared to the GB-IF method when R T ≤ 150 . However, when R T ≥ 150, the GB-IF method outperforms the GF-IF method. Depending on RT values used, 2–10 min would be required to resolve the WL ambiguities when using GNSS measurements with one second sampling rate.